APLIKASI SOLID PADA MEDIUM BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - Retno Ardiana S; Edison Anom; Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aims to find out the effect of solid aplication for seedling of oil palm and to find out the best dose for seedling oil palm growth in the main nursery. The research was conducted at the experimental farm of the Agriculture Faculty, University of Riau in June to October 2015. The experiment was arranged in completely randomized design (CRD) with six treatment, that is no solid aplication, 80 g/polybag solid aplication, 120 g/polybag solid aplication,160 g/polybag solid aplication, 200 g/polybag solid aplication, and 240 g/polybag solid aplication with three times replication. The data obtained were analyzed statiscally using analyze of variance and tested further by Duncan Multyple Range Test in 5% level. The result showed that solid aplication in oil palm medium significantly effect to increase of seeds height, increase number of leaves, increase of hump diameter, and dry weight of oil palm seedlings. 200 g/polybag solid aplication is the best dose for seedling oil palm growth in the main nursery   Keywords : Oil Palm, solid, main nursery